TBX2 expression is associated with platinum-sensitivity of ovarian serous carcinoma - Tasaka, Reiko (Oncol Lett, 2018)
The standard treatment for ovarian serous carcinoma comprises maximum debulking surgery and platinum-based chemotherapy. Despite the high response rate to chemotherapy, the majority of patients will be resistant to first-line agents and the prognosis for these patients is particularly poor. At present there are no reliable methods to determine or predict platinum resistance. T-box 2 (TBX2) is widely expressed in cancer cells and is involved in embryonic development and cell cycle regulation. TBX2 enables cells to bypass senescence through its ability to repress the cell cycle regulators p21 and p14(ARF); silencing TBX2 induces senescence. Ectopic expression of TBX2 is associated with conferred resistance to the DNA-damaging chemotherapeutic drugs cisplatin and doxorubicin. In the present study the association between TBX2 expression and platinum sensitivity was investigated. A total of 54 patients with ovarian serous carcinoma (FIGO stages III and IV) were treated at Osaka City University Hospital (Osaka, Japan) from January 2005 to December 2012. Patients were divided into platinum-sensitive (n=27) and resistant (n=27) groups, according to the platinum-free interval calculated from the last platinum administration to the time of recurrence. TBX2 expression in human ovarian serous carcinoma cells was inhibited by a TBX2-specific siRNA and changes in cisplatin and carboplatin sensitivity were determined. The TBX2-weighted score was significantly lower in the platinum-sensitive group than the platinum-resistant group (P=0.005) and the low TBX2 expression group was significantly more sensitive to platinum-based chemotherapy (P=0.004). Sensitivity to cisplatin and carboplatin significantly increased when TBX2 expression was inhibited in human ovarian serous carcinoma cells in vitro (P<0.05). TBX2 expression may serve as a predictive marker of the efficacy of platinum-based chemotherapy for patients with ovarian serous carcinoma.